TREATMENT OF ESSENTIAL HYPERTENSION WITH CALCIUM CHANNEL BLOCKERS: WHAT IS THE PLACE OF LERCANIDIPINE - Michel Burnier; Menno Pruijm; Gregoire Wuerzner (Российский кардиологический журнал)
In all actual clinical guidelines, dihydropyridine calcium channel blockers (CCBs) belong to the recommended first line antihypertensive drugs to treat essential hypertension. Several recent large clinical trials have confirmed their efficacy not only in lowering blood pressure but also in reducing cardiovascular morbidity and mortality in hypertensive patients with a normal or high cardiovascular risk profile. In clinical trials such as ALLHAT, VALUE or ASCOT, an amlodipine-based therapy was at least as effective, when not slightly superior, in lowering blood pressure and sometimes more effective in preventing target organ damages than blood pressure lowering strategies based on the use of diuretics, beta-blockers and blockers of the renin-angiotensin system. One of the main clinical side effects of the first and second generation CCBs including amlodipine is the development of peripheral edema. The incidence of leg edema can be markedly reduced by combining the CCB with a blocker of the renin-angiotensin system. This strategy has now led to the development of several fixed-dose combinations of amlodipine and angiotensin II receptor antagonists. Another alternative to lower the incidence of edema is to use CCBs of the third generation such as lercanidipine. Indeed, although no major clinical trials have been conducted with this compound, clinical studies have shown that lercanidipine and amlodipine have a comparable antihypertensive efficacy but with significantly less peripheral edema in patients receiving lercanidipine. In some countries, lercanidipine is now available in a single-pill association with an ACE inhibitor thereby further improving its efficacy and tolerability profile.